2017
DOI: 10.1093/toxsci/kfx019
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects of in utero exposure to di-(2-ethylhexyl)-phthalate (DEHP) in B6:129S4 mice

Abstract: Intrauterine exposure to phthalates is known to cause disorders of male reproductive function including androgen insufficiency, decreased fertility, and germ cell defects in rodents. In this study, we set out to investigate the effects of intrauterine exposure to di-(2-ethylhexyl)-phthalate (DEHP) on fetal development of the B6:129S4 mouse strain. Time-mated pregnant C57BL/6 dams were exposed to 0, 5, 250, or 500 mg/kg DEHP with corn oil as the vehicle via oral gavage from embryonic days (E)7 to 16. Survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…We also observed similar testicular abnormalities in F1 and F2 males derived from Oct4-deltaPE-GFP transgenic mice with a C57BL/6 background, which were used for isolating fetal testicular germ cells (figure supplement1A-D). In addition, a significant increase in the number of multinucleated germ cells was observed in embryonic day (E) 19.5 testis in animals prenatally exposed to DEHP compared with those in an oil-exposed group (figure supplement 1E, F), as reported previously (Ungewitter et al, 2017). These results indicated that our maternal DEHP exposure experiments reproduced the spectrum of testicular abnormalities described in a previous report (Doyle et al, 2013).…”
Section: Defects In Spermatogenesis Following Maternal Dehp Exposuresupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed similar testicular abnormalities in F1 and F2 males derived from Oct4-deltaPE-GFP transgenic mice with a C57BL/6 background, which were used for isolating fetal testicular germ cells (figure supplement1A-D). In addition, a significant increase in the number of multinucleated germ cells was observed in embryonic day (E) 19.5 testis in animals prenatally exposed to DEHP compared with those in an oil-exposed group (figure supplement 1E, F), as reported previously (Ungewitter et al, 2017). These results indicated that our maternal DEHP exposure experiments reproduced the spectrum of testicular abnormalities described in a previous report (Doyle et al, 2013).…”
Section: Defects In Spermatogenesis Following Maternal Dehp Exposuresupporting
confidence: 91%
“…We first administered pregnant mice with 300 mg/kg DEHP, which is the same dose as used in a previous study with C57BL/6 (Prados et al, 2015); however, we obtained few pups under those conditions, presumably reflecting embryonic lethality at this dose of DEHP. We then tested different doses of DEHP, and identified dose levels at which we could obtain pups that showed germ cell abnormalities in F1 and F2 offspring and in F1 embryos that were similar to those reported previously (Doyle et al, 2013;Stenz et al, 2017;Ungewitter et al, 2017) Using this experimental model, we identified a close correlation between DNA hypermethylation of spermatogenesis-related genes and their downregulation in F1 spermatogonia following maternal DEHP exposure (Fig 3). Previous reports have described promoter hypermethylation and downregulation of the Svs3ab gene, a gene that is involved in sperm motility, in the sperm of F1 males following maternal DEHP exposure (Stenz et al, 2017;Stenzid et al, 2019).…”
Section: Discussionsupporting
confidence: 70%
“…Lastly, the expression of Cyp17a1 gene was significantly down-regulated in the 500 mg/kg/day phthalate mixture group ( Figure 4B). Previous findings showed that prenatal exposure to 500 mg/kg/day DBP significantly decreased the expression of Cyp11a1, StAR, and Cyp17a1 (Shultz et al, 2001) and that prenatal exposure to 250 mg/kg/day DEHP significantly decreased the expression of Cyp17a1 and Hsd3b1 (Ungewitter et al, 2017). Taken together, these results suggest that the low serum testosterone levels seen in the phthalate mixture exposure group may be primarily due to adversely affected testicular steroidogenesis.…”
Section: Prenatal Exposure To Phthalate Mixture Disrupts Testicular Smentioning
confidence: 52%
“…The potential for DEHP to cause miscarriages is supported by our data indicating that ancestral DEHP exposure increased mid-gestation infertility in the F2 generation. Further, the potential of DEHP to cause miscarriages is supported by a study showing that DEHP exposure (250 and 500 Early gestation 3 6 5 0 3 Mid gestation 3 3 5 3 2 Late gestation 0 0 1 2 2 F2 Early gestation 6 3 2 1 2 Mid gestation 2 2 0 11 2 Late gestation 0 0 0 0 2 F3 Early gestation 3 2 1 1 4 Mid gestation 2 1 1 3 1 Late gestation 0 1 1 0 0 mg/kg/day) is teratogenic and has a lethal impact on the mouse fetus (Ungewitter et al, 2017). We have previously shown that ancestral exposure to DEHP decreased serum progesterone levels in young adult mice (Rattan et al, 2018) and at 1 year of age in the F2 generation (Brehm et al, 2018).…”
Section: Discussionmentioning
confidence: 99%